2018
DOI: 10.1111/cas.13547
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T lymphocyte response to peptide vaccination predicts survival in stage III colorectal cancer

Abstract: We previously reported a phase I clinical trial of a peptide vaccine ring finger protein 43 (RNF43) and 34‐kDa translocase of the outer mitochondrial membrane (TOMM34) combined with uracil‐tegafur (UFT)/LV for patients with metastatic colorectal cancer (CRC), and demonstrated the safety and immunological responsiveness of this combination therapy. In this study, we evaluated vaccination‐induced immune responses to clarify the survival benefit of the combination therapy as adjuvant treatment. We enrolled 44 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Interestingly, only one patient failed to mount specific CD8 T cell responses against RNF43 and/or TOMM34 and 83% of patients had stable disease following the vaccination (165). After having demonstrated the safety and immunological responsiveness of this combination therapy, the same group showed that 3-years DFS was significantly better in the group of patients with CD8 T cell responses than in the group without (154,166). In order to improve clinical responses, Okuno et al added to this original combination therapy 5 other TAA-derived peptides to the vaccine.…”
Section: Tumor-associated Antigens and Neoantigens In Crc Vaccinationmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, only one patient failed to mount specific CD8 T cell responses against RNF43 and/or TOMM34 and 83% of patients had stable disease following the vaccination (165). After having demonstrated the safety and immunological responsiveness of this combination therapy, the same group showed that 3-years DFS was significantly better in the group of patients with CD8 T cell responses than in the group without (154,166). In order to improve clinical responses, Okuno et al added to this original combination therapy 5 other TAA-derived peptides to the vaccine.…”
Section: Tumor-associated Antigens and Neoantigens In Crc Vaccinationmentioning
confidence: 97%
“…Lastly, peptide vaccines are based on the identification and synthesis of antigenic epitopes derived from TAAs able to induce specific antitumor responses (146). Numerous studies have identified TAAs expressed by CRC cells as potential targets for vaccine immunotherapy, including but not limited to CEA (147,148), WT1 (149), MUC1 (150), survivin-2B (151,152), RNF43 (153,154), TOMM34 (154), 5T4 (155,156), GUCY2C (157), SART3 (158), and hTERT (159). CEA is the most extensively explored target in CRC vaccine trials and numerous phase I studies have involved CEA mRNA or CEA peptides loaded onto DCs.…”
Section: Tumor-associated Antigens and Neoantigens In Crc Vaccinationmentioning
confidence: 99%
“…In these cancers, Tomm34 promotes colorectal cancer cell growth [21] and is a biomarker of poor outcome in early invasive breast cancer [22] and bladder cancer [26]. As a tumour-associated protein, Tomm34 peptide vaccination is under investigation as a therapeutic option for colorectal cancer, with significant Tomm34 cytotoxic T-lymphocyte (CTL) response observed [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In some situations, cell‐based immunotherapy offers a valuable and more effective alternative to conventional cytotoxic therapy . A series of studies have demonstrated the efficacy of adoptive cell immunotherapy, including tumor‐infiltrating lymphocytes, antigen‐specific T lymphocytes, cytokine‐induced killer (CIK) cells and chimeric antigen receptor (CAR) T cells . Among them, CIK cells have characteristics of rapid proliferation, strong antitumor activity, broad spectrum of antitumor activity and minimal toxicity and have been demonstrated as effective in many tumors, including CRC .…”
Section: Introductionmentioning
confidence: 99%
“…4,7 A series of studies have demonstrated the efficacy of adoptive cell immunotherapy, including tumorinfiltrating lymphocytes, antigen-specific T lymphocytes, cytokine-induced killer (CIK) cells and chimeric antigen receptor (CAR) T cells. [8][9][10][11] Among them, CIK cells have characteristics of rapid proliferation, strong antitumor activity, broad spectrum of antitumor activity and minimal toxicity and have been demonstrated as effective in many tumors, 12 including CRC. 11,[13][14][15] Moreover, our previous studies demonstrated the feasibility and low toxicity of CIK cell treatment for several kinds of cancer, including hepatocellular carcinoma, 16 breast cancer, 17,18 epithelial ovarian cancer, 19 non-small-cell lung cancer 20 and nasopharyngeal carcinoma.…”
Section: Introductionmentioning
confidence: 99%